Islamic banks, deposit insurance reform, and market discipline: evidence from a natural framework - Aysan, Ahmet F.; Disli, Mustafa; Duygun, Meryem; Ozturk, Huseyin (Springer, 2016)
Although it has been intensively claimed that Islamic banks are more subject to market discipline, the empirical literature is surprisingly mute on this topic. To fill this gap and to verify the conjecture that Islamic bank depositors are indeed able to monitor and discipline their banks, we use Turkey as a test setting. The theory of market discipline predicts that when excessive risk taking occurs, depositors will ask higher returns on their deposits or withdraw their funds. We look at the effect of the deposit insurance reform in which the dual deposit insurance was revised and all banks were put under the same deposit insurance company in December 2005. This gives us a natural experiment in which the effect of the reform can be compared for the treatment group (i.e., Islamic banks) and control group (i.e., conventional banks). We find that the deposit insurance reform has increased market discipline in the Turkish Islamic banking sector. This reform may have upset the sensitivities of the religiously inspired depositors, and perhaps more importantly it might have terminated the existing mutual supervision and support among Islamic banks.